2016
DOI: 10.1007/s10584-016-1794-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sources of uncertainty in projected hydrological changes under climate change in 12 large-scale river basins

Abstract: This paper aims to evaluate sources of uncertainty in projected hydrological changes under climate change in twelve large-scale river basins worldwide, considering the mean flow and the two runoff quantiles Q 10 (high flow), and Q 90 (low flow). First, changes in annual low flow, annual high flow and mean annual runoff were evaluated using simulation results from a multi-hydrological-model (nine hydrological models, HMs) and a multi-scenario approach

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 223 publications
(144 citation statements)
references
References 36 publications
10
134
0
Order By: Relevance
“…Additionally, the current study simulated the hydrological variables via a single hydrological model, and a study conducted by Vetter et al . () noted that the uncertainty arising from the multiple hydrological models was relatively less. In contrast, Bastola et al .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the current study simulated the hydrological variables via a single hydrological model, and a study conducted by Vetter et al . () noted that the uncertainty arising from the multiple hydrological models was relatively less. In contrast, Bastola et al .…”
Section: Discussionmentioning
confidence: 99%
“…We used only one hydrological model, which is also a source of uncertainty. However, variation in climate signals between GCMs and emissions scenarios, particularly precipitation projections, may be a larger source of uncertainty than the choice of hydrology model (Thompson et al, 2014;Vetter et al, 2016).…”
Section: Sources Of Uncertaintymentioning
confidence: 99%
“…As a consequence, several studies have shown the impacts of future climate change on freshwater budgets [5,[33][34][35][36], streamflow [2,6,7,37,38], and hydrological extremes [6,[8][9][10]39,40] at large-scale continental watersheds. In small-scale Pacific island watersheds, such as in Hawaii, a few studies [3,4,41] have also assessed the impact of climate change on water budgets but focused at monthly and yearly mean values.…”
Section: Introductionmentioning
confidence: 99%